1998
DOI: 10.1111/j.1600-0714.1998.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A and hydroxycyclosporine (M‐17) affect the secretory phenotype of human gingival fibroblasts

Abstract: The responsiveness of human gingival fibroblast populations to cyclosporin A (CsA) and its principal metabolite, hydroxycyclosporine (M17), was evaluated in cell culture. Gingival fibroblasts exhibited a dose‐dependent accumulation and bell‐shaped distribution of dansylated CsA. A 100‐fold excess of non‐labeled CsA prevented the accumulation of the fluorescent probe in the fibroblasts. Both CsA (400 ng/ml) and M17 (100 ng/ml) stimulated mean gingival fibroblast cell number to 23.2% and 36.7% above controls, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
9
1
2
Order By: Relevance
“…CsA exposure had no effects on cell proliferation. Our results differed from those of several studies which have demonstrated that CsA stimulates the proliferation of HGFs (Mariotti et al , 1998; Cotrim et al , 2003) and rat gingival fibroblasts (Yoshida et al , 2005). However, similar studies were reported previously that CsA had no effects on cell proliferation in lower doses and inhibited cell growth in higher doses in HGFs (James et al , 1995; Yamaguchi et al , 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…CsA exposure had no effects on cell proliferation. Our results differed from those of several studies which have demonstrated that CsA stimulates the proliferation of HGFs (Mariotti et al , 1998; Cotrim et al , 2003) and rat gingival fibroblasts (Yoshida et al , 2005). However, similar studies were reported previously that CsA had no effects on cell proliferation in lower doses and inhibited cell growth in higher doses in HGFs (James et al , 1995; Yamaguchi et al , 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of the cyclosporin A on the proliferation of human gingival fibroblasts are controversial; several studies have demonstrated that cyclosporin A stimulates the proliferation (1, 3–5), whereas one study has reported that cyclosporin A suppresses this proliferation (2). In these studies, gingival cells obtained from male or female humans with a wide range of ages from 17 to 67 years old were used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 23–25% increases seem to be small in comparison with the report that the administration of cyclosporin A to rats enlarged the cross‐sectional area of the gingival tissue by more than 150% (25). In addition, an abnormal synthesis of collagen and other extracellular matrix components (3, 4, 26), and a decline of collagen turnover via changes in the matrix metalloproteinases and tissue inhibitors of metalloproteinase (9, 27, 28) reportedly occur in association with cyclosporin A‐induced gingival outgrowth. Thus, the mechanism by which cyclosporin A induces the gingival outgrowth is probably comprised of several factors, and includes the enhancement of gingival cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that the increase in extracellular matrix is not well understood in cyclosporin A‐induced gingival overgrowth, there is no evidence of the expression of heparan sulfate proteoglycans, such as syndecans and betaglycan, in this lesion. Only generic evaluations of proteoglycans and glycosaminoglycans have been published (20–23). In a previous study, we observed a higher expression of the proteoglycan perlecan, found in basement membranes (24).…”
mentioning
confidence: 99%